Primary Cilia and Centrosomes in Neocortex Development - Wilsch-Bräuninger, Michaela; Huttner, Wieland B. (Frontiers in Neuroscience, 2021)
During mammalian brain development, neural stem and progenitor cells generate the neurons for the six-layered neocortex. The proliferative capacity of the different types of progenitor cells within the germinal zones of the developing neocortex is a major determinant for the number of neurons generated. Furthermore, the various modes of progenitor cell divisions, for which the orientation of the mitotic spindle of progenitor cells has a pivotal role, are a key parameter to ensure the appropriate size and proper cytoarchitecture of the neocortex. Here, we review the roles of primary cilia and centrosomes of progenitor cells in these processes during neocortical development. We specifically focus on the apical progenitor cells in the ventricular zone. In particular, we address the alternating, dual role of the mother centriole (i) as a component of one of the spindle poles during mitosis, and (ii) as the basal body of the primary cilium in interphase, which is pivotal for the fate of apical progenitor cells and their proliferative capacity. We also discuss the interactions of these organelles with the microtubule and actin cytoskeleton, and with junctional complexes. Centriolar appendages have a specific role in this interaction with the cell cortex and the plasma membrane. Another topic of this review is the specific molecular composition of the ciliary membrane and the membrane vesicle traffic to the primary cilium of apical progenitors, which underlie the ciliary signaling during neocortical development; this signaling itself, however, is not covered in depth here. We also discuss the recently emerging evidence regarding the composition and roles of primary cilia and centrosomes in basal progenitors, a class of progenitors thought to be of particular importance for neocortex expansion in development and evolution. While the tight interplay between primary cilia and centrosomes makes it difficult to allocate independent roles to either organelle, mutations in genes encoding ciliary and/or centrosomal proteins indicate that both are necessary for the formation of a properly sized and functioning neocortex during development. Human neocortical malformations, like microcephaly, underpin the importance of primary cilia/centrosome-related processes in neocortical development and provide fundamental insight into the underlying mechanisms involved.